Luther on Conversion : The Early Years - Harran, Marilyn (Cornell University Press, 2019)
What is conversion? How does it come about? What preparations must a person make? Harran traces the evolution of Luther's views on these questions, treating his early years as an Augustinian monk, the beginnings of his work as a reformer, and his final evangelical breakthrough, during which he realized the full theological implications of his religious stance. Harran studies Luther's changing interpretations of conversion in his exegetical writings on the Psalms, Romans, Hebrews, and Galatians, in sermons and letters, and in early reform writings, and she considers the relation of conversion to faith, justification, and grace, concepts traditionally viewed as the cornerstones of Luther's mature theology. Introducing new and compelling evidence to the heated debate about Luther's own conversion, she analyzes the accuracy of his later recollections of his "Tower Experience" and its dating.Insightful and innovative, Luther on Conversion will be welcomed by anyone interested in Luther and in the revolution in faith that he brought about.